E-Learning Usage Analysis in English Language in Universitas Muhammadiyah Purworejo - Indra Kusuma; Abdul Ngafif; Edi Sunjayanto Masykuri (Scripta : English Department Journal, 2021)
This research belongs to qualitative research. The objectives of this research are to explain E-learning usage and to determine of the students’ responses E-learning Usage in English Language Education of Universitas Muhammadiyah Purworejo. The unit of analysis of this research is E-learning usage at the students of English Language Education. The subject of this research were the English education students of batch 2016, 2017, 2018, 2019 of Universitas Muhammadiyah Purworejo. There are 43 students which are volunteering in answering the questionnaire. The result of the analysis shows that E-learning is easy to use (51,1%), E-learning perceives usefulness (37,2%), E-learning makes their communication and interaction easier and comfortable (48%), and students feel satisfy with E-learning (37,4%). That mean the result of the questionnaire most of them feeling easy and comfortable using E-learning method and the result of this research shows that E-learning is useful and helpful for the students and they felt satisfied with E-learning.